Read Aloud Sebagai Sarana Pengembangan Bahasa Anak Usia Dini: Studi Literatur - Zulaeha, Vita Siti; Setiasih, Ocih (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Early childhood language development can be influenced by interactions between children and their environment. Interactions that occur can stimulate children's language development. Children's language skills can be stimulated through various methods. One method that parents and educators can use is the read aloud method. Read aloud activities are reading aloud activities that involve not only hearing but also the interaction between the reader and the child. This method can stimulate early childhood language development through verbal interactions between readers or facilitators of read-aloud activities with children. The purpose of this study is to explore the role of the read-aloud method in developing early childhood language skills through a literature study approach. This literature review examines previous research that shows that read aloud helps children's language development through ongoing discussion of new words and sentence structures. The research method used in the research is a literature study. The data collection technique used in this research is to search for articles on trusted sources. In collecting data, researchers searched for sources as many as 65 literature. Then selected articles related to the read aloud method in improving early childhood language skills. As a result, 12 articles were selected for analysis.